EVALUASI KINERJA SIMPANG BERSINYAL PADA SIMPANG TOHPATI - Kariyana, I Made (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
This paper aims to determine the evaluation of a signalized intersection located at the Tohpati Denpasar intersection. This research is motivated by the difficulty of problems at the intersection point which is the center of meeting of vehicle flows from various directions. One of the intersections using APILL is the Tohpati intersection. The purpose of installing APILL is to provide an opportunity for each road user to take turns in order to pass the intersection in an orderly manner. However, there are still long queues and high delays that occur causing congestion on each arm of the intersection, this makes the presence of APILL at the intersection considered ineffective and the performance of the intersection is no longer effective. This research uses a quantitative type method with a field study approach. This research concludes that the results of the analysis show that the highest value of the delay at morning peak hours is on Jl. The Ngurah Rai bypass is worth 120.5 seconds/pcu for a traffic volume of 831 vehicles/hour and a queue length of 116 m. Furthermore, for peak hours during the day, the highest delay is on Jl. Gatot Subroto Timur with a value of 75.04 sec/smp which occurred due to a current of 940 pcu/hour passing through the approach with a queue of 116.67 m. Then the highest delay for afternoon peak hours is on Jl. Bypass Ngurah Rai with a value of 308.92 seconds/pcu which resulted in a current of 1,293 pcu/hour with a queue length of 140 m. The results of the analysis show that this year's research and the previous year's research had the same results where the level of service at the Tohpati intersection was F.